Analisis Praktik Dan Pemahaman Masyarakat Terhadap Pembacaan Yasin 41 (Studi Living Quran Di Desa Besilam Kecamatan Padang Tualang Kabupaten Langkat) - Ahliya, Syahra; Darta, Ali (Kamaya: Jurnal Ilmu Agama, 2024)
The phenomenon of the practice of reciting Yasin 41 is carried out in Besilam Village, Padang Tualang District, North Sumatra. This practice is carried out if someone has a special desire or desire to ask and beg to Allah through reading Yasin 41 times. The purpose of this study is to reveal how the practice of reciting Yasin 41, how the community understands the practice of reciting Yasin 41 and the impact felt by the community. This research method uses the approach of living quran studies and field research (library research), namely by going directly to the research location to understand various aspects of the practice of reading yasin 41 in Besilam village. The data sources used are primary and secondary data. The data collection techniques used by the author are interviews, observation, and documentation. The results of the study revealed that the practice of reading yasin 41 is carried out every day after finishing the morning prayer, this practice is understood to have an important meaning, namely, the practice of spiritual worship that reassures the soul of the readers. In addition, this practice makes a significant contribution to the study of the Living Quran by providing concrete examples of how Quranic verses are practised in social and cultural contexts. The researcher also gained deeper insights into the interaction of Muslims with their sacred texts, the preservation of Islamic and spiritual traditions, and the influence of Quranic verses in the lives of Muslim communities. Thus, the practice of reciting Yasin 41 not only enriches the academic understanding of the Living Quran but also shows the dynamic life and sustainability of the sacred text in Muslim societies.